1971
DOI: 10.1002/ange.19710831307
|View full text |Cite
|
Sign up to set email alerts
|

Neuartige asymmetrische Cyclisierung zu optisch aktiven Steroid‐CD‐Teilstücken

Abstract: Im Gegensatz zur oben beschriebenen Oxidation der acyclischen Selenoxo-phosphorane (2) ist die Oxidation der diastereomeren 2-Methoxy-4-methyl-4H-5,6-dihydro-1,3,2-dioxaphosphorin-2-selenide ( 4 ) zu den Oxiden ( 5 ) [91 stark stereospezifisch ; eine Epimerisierung wurde nicht beobachtet"']. + trans-i4i cis -(4) truns-(4) cis-(4) Reagens trans-(5) cis-(5) (%) (%I (%) (%) 83.5 16.5 N*O, 79.0 21.0 83.5 16.5 HNO, 81.0 19.0 22.0 78.0 N204 25.0 75.0 22.0 78.0 HNO, 25.0 75.0 -. .~ .-Die Synthese von optisch aktiven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0
23

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(107 citation statements)
references
References 2 publications
0
84
0
23
Order By: Relevance
“…Instead, its results pointed to an exceptional sensitivity to conditions of the stereochemical outcome of such a reaction. This implied that no conclusion could be drawn from the model study with regard to the mechanism of the stereoselection observed by Hajos and Parrish [11], and by Eder et al [12].…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Instead, its results pointed to an exceptional sensitivity to conditions of the stereochemical outcome of such a reaction. This implied that no conclusion could be drawn from the model study with regard to the mechanism of the stereoselection observed by Hajos and Parrish [11], and by Eder et al [12].…”
Section: Methodsmentioning
confidence: 92%
“…While the N-acyl derivatives of type 3 are quite stable 12 ), the bicyclic oxazolidinones 2 are difficult to purify and isolate on a preparative scale 13 ) for two reasons: i) They must be handled under exclusion of moisture; neat liquid samples or solutions in common organic solvents turn cloudy on contact with air, due to formation of the insoluble amino acids. ii) They undergo decarboxylation at elevated temperatures, with generation of azomethine ylides, which can be trapped by dipolarophiles 14 ), as shown for oxazolidinone 2a in the reaction with tetrakis(methoxycarbonyl)ethylene (!…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the optimization of activity and selectivity, directed-evolution methodologies (combined with an efficient selection or screening tool) outperform combinatorial ligand libraries. [3][4][5][6][7][8][9][10][11][12][13] With the hope of alleviating some of the inherent limitations of both enzymatic and organometallic catalysis, two approaches have recently witnessed a revival: 1) organocatalysis [14][15][16][17][18][19] and 2) artificial metalloenzymes based on either covalent [20,21] or supramolecular anchoring [22] of a catalytic moiety in a macromolecular host. [23][24][25][26][27][28][29][30] Inspired by the early works of Whitesides and Wilson, [22] we recently reported artificial metalloenzymes based on the biotin-avidin technology.…”
mentioning
confidence: 99%
“…1,2 Beginning from the discovery of the L-proline-catalyzed aldol reaction, [3][4][5] over the years, it evolved into a general strategy for the activation of carbonyl compounds. Ten years ago, this mode of activation was limited to the formation of enamines and iminium ions as intermediates (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%